2016
DOI: 10.1007/s10826-016-0499-1
|View full text |Cite
|
Sign up to set email alerts
|

Parental Psychopathology in Families of Children with ADHD: A Meta-analysis

Abstract: There is a large body of literature that examines the association between parental psychopathology and child ADHD. The strength of the relationship varies across studies due to differences between the sample characteristics and methodologies utilized. A meta-analysis was conducted to evaluate the strength of the association between parental psychopathology and ADHD to review the research findings and to establish the degree and size of the effect. The Tables Table 1: Neurodevelopmental disorders are b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 92 publications
(147 reference statements)
1
36
1
1
Order By: Relevance
“…The role of stress in dysfunctional parenting has been documented in a number of populations, including parental depression and community samples (Pinderhughes, Dodge, Bates, Pettit, & Zelli, 2000;Venta, Velez, & Lau, 2016). When compared to parents of children without ADHD, parents of children with ADHD experience higher levels of stress (Modesto-Lowe, Danforth, & Brooks, 2008), with such stress associated with psychopathology including depression (Cheung & Theule, 2016) and engagement in suboptimal parenting, specifically greater parent-child conflict and parenting anger (Bhide, Sciberras, Anderson, Hazell, & Nicholson, 2019;Theule et al, 2013). Our study did not measure parenting behaviors, but future research should examine whether dysfunctional parenting practices known to relate to parent stress mediate the relationships seen here.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of stress in dysfunctional parenting has been documented in a number of populations, including parental depression and community samples (Pinderhughes, Dodge, Bates, Pettit, & Zelli, 2000;Venta, Velez, & Lau, 2016). When compared to parents of children without ADHD, parents of children with ADHD experience higher levels of stress (Modesto-Lowe, Danforth, & Brooks, 2008), with such stress associated with psychopathology including depression (Cheung & Theule, 2016) and engagement in suboptimal parenting, specifically greater parent-child conflict and parenting anger (Bhide, Sciberras, Anderson, Hazell, & Nicholson, 2019;Theule et al, 2013). Our study did not measure parenting behaviors, but future research should examine whether dysfunctional parenting practices known to relate to parent stress mediate the relationships seen here.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent meta-analysis of 80 studies examining parents' experiences of caring for a child with ADHD, parents reported exhaustion, anxiety, anger, desperation, and helplessness, reflecting high levels of daily stress (Corcoran, Schildt, Hochbrueckner, & Abell, 2017). Compared to parents of children without ADHD, parents of children with ADHD display higher rates of substance-related disorders as well as depression and anxiety (Cheung & Theule, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…As concerns mental health, parents of children with ADHD report more psychological disorders then parents of children without ADHD, in particular depression, anxiety and alcohol abuse (Cheung & Theule, 2016;Durukan, Kara, Almbaideen, Karaman, & GĂŒl, 2018;Faraone & Biederman, 1997;Margari, et al, 2013) and higher levels of stress than parents of children with learning disabilities or with typical development (Baker & McCal, 1995;Fisher, 1990). Prominent stress related factors include child symptoms' severity and behavioral disturbance, major and minor life events, as well as parents' psychological characteristics (such as perceived parental control over child behaviors and self-esteem), and parental psychological disorders ( Fischer, 1990;Harrison & Sofronoff, 2002;Mash & Johnston, 1983;Theule, Wiener, Tannock, Jenkins, 2013;Vitanza & Guarnaccia, 1999).…”
Section: Adhd: a Challenge For Parentsmentioning
confidence: 99%
“…However, data are inconsistent because other studies did not find the same differences in psychopathology between parents of children with ADHD and parents of children in the control group, suggesting the need to further investigate this controversial issue (20). A recent meta-analysis showed that the research on these topics has largely focused on mothers, with fewer studies on fathers (21).…”
Section: Introductionmentioning
confidence: 99%